2005
DOI: 10.1080/00015550510026352
|View full text |Cite
|
Sign up to set email alerts
|

Thymus is Enlarged in Children with Current Atopic Dermatitis. A Cross-sectional Study

Abstract: Atopic dermatitis is a common skin disorder of unknown aetiology with peak incidence in early childhood. The disease is associated with peripheral T-cell accumulation in the skin. The thymus is a key organ of the cellular immune response early in life. We hypothesized that atopic dermatitis is associated with an unbalanced establishment of the peripheral T-lymphocyte system. This cross-sectional study was performed to compare thymus sizes in patients with atopic dermatitis and healthy controls. Thirty-seven ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…[4] These cells can be detected in a significant proportion in the peripheral blood of children with AD. [1] This may suggest a faulty maturation of the T-lymphocyte system as a basic pathophysiological change in AD, leading to skin inflammation with CD4 + CD8 + T lymphocytes resembling immature T cells. [21] This is likely to lead to the skewing of many immune reactions in those patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] These cells can be detected in a significant proportion in the peripheral blood of children with AD. [1] This may suggest a faulty maturation of the T-lymphocyte system as a basic pathophysiological change in AD, leading to skin inflammation with CD4 + CD8 + T lymphocytes resembling immature T cells. [21] This is likely to lead to the skewing of many immune reactions in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that AD is associated with an unbalanced establishment of the peripheral T-lymphocyte system. Cutaneous lymphocyte-associated antigen (CLA)[1] is a cell surface glycoprotein that has been postulated to play an important role in T-cell migration and homing to the skin. It has been proposed that interaction between T cells and epidermal keratinocytes plays a central role in the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: ktp56@hotmail.com Atopic dermatitis (AD) is a disorder with accumulation of activated T cells in the skin and, in some patients, increased IgE production leading to type I allergies to environmental allergens (1). We have demonstrated a significant increase in thymic volume in infants and children with active AD, an increased number of lymphocytes in the skin, an increased telomerase activity and shortened telomere length in T cells both in blood and skin, and an increased number of double-positive CD4+CD8+ T cells in peripheral blood (2)(3)(4)(5). These results suggest that patients with AD have a dysregulation of thymic T-cell selection and emission ( 6) and increased T-cell turn-over in the peripheral immune system.…”
Section: Cd8+ T-cell Subpopulation Because Both Atopic Dermatitis And...mentioning
confidence: 84%
“…In one study it was shown that thymus size declined with age in both children with atopic dermatitis and healthy controls. However, the size of the thymus among children with active atopic dermatitis was higher compared to healthy controls [ 3 ]. Having a smaller thymus may be an advantage for TM patients, who are prone to alloimmunization related to transfusion.…”
Section: To the Editormentioning
confidence: 99%